Properties of Self-Consolidating Concrete Produced Using Local Algerian Materials - Nasr-eddine Bouhamou; Nadia Belas; Ahmed Attar; Belkacem Achour; Abdelkader Mebrouki (Journal of Construction in Developing Countries, 2011)
This paper describes an experimental investigation of the effects of the Water/Cement ratio on the behaviour of self-consolidating concrete in the fresh and hardened states, using local Algerian materials. Several tests were carried out to characterise the properties of these concretes: spread flow, L-box test, stability assessment with sieve, bleeding, mechanical strength, shrinkage and microstructural studies that encompassed both mineralogical characterisation and porometric distributions. The results offer important insight into the optimisation of the rheological characteristics of self-consolidating concrete. They also permit the development of a variety of formulations that meet rheological requirements such as good deformability, reduced bleeding and the absence of segregation.